Effect of endurance training on the VO2-work rate relationship in normoxia and hypoxia - Prieur, F.; Benoit, H.; Busso, T.; Castells, J.; Denis, C. (Medicine & Science in Sports & Exercise, 2005)
Purpose: We postulated that the relationship between [latin capital V with dot above]O2 and work rate ([latin capital V with dot above]O2-WR relationship) during incremental exercise is dependent on O2 availability, and that training-induced adaptations alter this relationship. We therefore studied the effect of endurance training on [latin capital V with dot above]O2 response during incremental exercise in normoxia and hypoxia (FIO2 = 0.134).